2019
DOI: 10.1029/2019gl082611
|View full text |Cite
|
Sign up to set email alerts
|

Pathways for Ecological Change in Canadian High Arctic Wetlands Under Rapid Twentieth Century Warming

Abstract: We use paleoecological techniques to investigate how Canadian High Arctic wetlands responded to a mid‐twentieth century increase in growing degree days. We observe an increase in wetness, moss diversity, and carbon accumulation in a polygon mire trough, likely related to ice wedge thaw. Contrastingly, the raised center of the polygon mire showed no clear response. Wet and dry indicator testate amoebae increased concomitantly in a valley fen, possibly relating to greater inundation from snowmelt followed by inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 102 publications
(109 reference statements)
0
14
1
Order By: Relevance
“…These dynamics in turn cause climate feedbacks, particularly by affecting carbon cycling and release of greenhouse gases (Pearson et al, 2013; Ratcliffe et al, 2017; Schuur et al, 2015). However, the scale of this transformation is not uniform across northern landscapes (Sim et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…These dynamics in turn cause climate feedbacks, particularly by affecting carbon cycling and release of greenhouse gases (Pearson et al, 2013; Ratcliffe et al, 2017; Schuur et al, 2015). However, the scale of this transformation is not uniform across northern landscapes (Sim et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously reported that different peatland habitats may also undergo different peatland-climate feedback pathways (Zhang et al, 2020). Any one site-based discussion of regional feedbacks is likely to be biased because different peatland types can experience specific successions under similar climate conditions, such as the differences observed between palsa K1P and fen K2 in region Kuujjuarapik in this study, let alone different regions that have different climate (Sim et al, 2019). This problem is exacerbated when within-site data, even taken from a consistent microform, is also variable.…”
Section: Future Perspective On Detecting Reliable Peatland-climate Fementioning
confidence: 77%
“…Testate amoebae have become an important tool for reconstruction of palaeohydrology from temperate (Booth 2002;Gałka et al 2013;Hendon and Charman 2004), tropical (Swindles et al 2018(Swindles et al , 2016(Swindles et al , 2014, and high latitude (Sim et al 2019;Swindles et al 2015;Zhang et al 2018) peatlands. Some testate amoeba taxa produce proteinaceous tests (amorphous, e.g.…”
Section: Introductionmentioning
confidence: 99%